2014
DOI: 10.1107/s2052520614017570
|View full text |Cite|
|
Sign up to set email alerts
|

First experimental charge density study using a Bruker CMOS-type PHOTON 100 detector: the case of ammonium tetraoxalate dihydrate

Abstract: The aim of this study was to test the applicability of a Bruker AXS CMOS-type PHOTON 100 detector for the purpose of a fine charge density quality data collection. A complex crystal containing oxalic acid, ammonium oxalate and two water molecules was chosen as a test case. The data was collected up to a resolution of 1.31 Å(-1) with high completeness (89.1%; Rmrg = 0.0274). The multipolar refinement and subsequent quantum theory of atoms in molecules (QTAIM) analysis resulted in a comprehensive description of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
3
3
0
Order By: Relevance
“…In the C­(7I)O­(1I) bond, a carbonyl group belonging to INH, there is a good agreement between experimental and theoretical results, although O­(1I) is also involved in H-bonds with neighboring molecules. The values obtained for the C–O bonds are close to those reported in the literature. ,,,, …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the C­(7I)O­(1I) bond, a carbonyl group belonging to INH, there is a good agreement between experimental and theoretical results, although O­(1I) is also involved in H-bonds with neighboring molecules. The values obtained for the C–O bonds are close to those reported in the literature. ,,,, …”
Section: Resultssupporting
confidence: 89%
“…Both C–O bonds in the cocrystal present a high electron density at the BCP, which, along with the small bond path length (1.24 Å), are interpreted as double bonds, in agreement with the values reported in the literature. ,, Concerning C­(2F)O­(2F) from 5FC, there is a good agreement between the experimental electron density and the periodic calculation. The gas-phase calculation, on the other hand, presents a higher electron density, especially considering the isolated 5FC molecule.…”
Section: Resultssupporting
confidence: 88%
“…Careful examination indicated that mostly the high-angle data are responsible for the presence of these spurious features suggesting that the observed model deficiencies are related to some inappropriate thermal motion description of this atom. Indeed, we were able to take these effects successfully into account by refining the third-order Gram–Charlier parameters (Figure b). All the final refinement statistics are summarized in Table , whereas more details are available in the Supporting Information. The CIF file is present in the Supporting Information, or can be retrieved from the Cambridge Structural Database (CSD) , (deposition number: CCDC 1814107).…”
Section: Methodsmentioning
confidence: 99%
“… a Definition of R mrg is the same as in our previous papers, , and follows Blessing’s definitions used in the SORTAV program. b Number in parentheses constitutes the percentage of the “observed” (i.e., with I ≥ 3σ­( I )) unique reflections with respect to the total number of unique reflections. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation